KOLABORASI BERDAYA: WORKSHOP FOTOGRAFI DAN FESTIVAL LITERASI NUMERASI PERKUAT KREATIVITAS PESERTA DIDIK PKBM - Yuniardi, Amalia; Septiana Hapsari Putri; Rahmi Hidayati; Jakiya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The “Empowering Collaboration” activity, consisting of a Photography Workshop and Numeracy Literacy Festival at PKBM Insan Mandiri Gemilang, was carried out to improve students' abilities through collaborative, creative, and hands-on methods. This study used a qualitative approach with participatory methods to explore the planning process, implementation, and impact of activities on literacy, numeracy, creativity, digital literacy, and character development. The results showed that numeracy literacy improved participants' ability to process information, perform simple calculations, and think critically. The photography workshop significantly increased visual creativity and the use of digital technology. In addition, art and tahfidz activities also play a role in developing self-confidence, discipline, and cooperation skills. Overall, the “Empowering Collaboration” activity has been proven to increase learning motivation, active participation, and the empowerment of students, making it an innovative learning model in non-formal education.